NEGOTIATION IN WEDDING PROPOSAL CEREMONY (AN ETHNOGRAPHY OF COMMUNICATION STUDY IN MINANGKABAU SOCIETY IN SOLOK REGENCY WEST SUMATERA) - Marta, Redo Andi; Rafli, Zainal (INTERNATIONAL JOURNAL OF LANGUAGE EDUCATION AND CULTURE REVIEW, 2016)
This research aimed to explain the way and culture of utterances in wedding proposal ceremony in Minangkabau. This research was qualitative research using ethnography of communication method. The findings of the research can be described as follow. First is the negotiation using turn taking in own initiative. However before the agreement was taken using own initiative, the discussion need to be done. The culture of discussion is the culture of Minangkabau society to get an agreement. It is because the decision made will give effect to other family members. Second is negotiation that always used in direct utterance in form of declarative utterance. Third is negotiation that always used in indirect utterance in form of declarative and imperative utterance. Indirect utterance was the utterance that mostly used. This is related with the culture of Minangkabau society that has intrinsic meaning.